심층 인터뷰를 통한 대학생들의 기부 활동 인식에 대한 탐색적 연구 - SNS 기부활동을 중심으로 - 엄남현(Namhyun Um) (한국콘텐츠학회 논문지, 24(7), 2024)
본 연구에서는 심층 인터뷰 방식을 통해 대학생들의 기부 동기와 이유는 무엇이고, SNS 기부의 장점과 SNS 기부 시 고려 사항은 무엇인지 밝혀내고자 했다. 본 연구결과, 기부동기는 내적동기와 외적동기로 구분되었으며, 내적동기에는 이타심, 동정심, 그리고 사회적 책임감 등이 있었으며, 외적동기로는 지인의 권유, 광고, 가족의 권유, 연예인 기부활동 등이 있었다. 대학생들의 기부이유는 자신의 기부가 성숙한 사회로 나아가는데 도움이 될 것이라 생각하는 순수한 기부 이유와 사회에 도움이 될 수 있는 기부를 한다는 것에 대한 뿌듯함 마음을 가지는 이타적인 이유가 공존했다. 대학생들은 SNS 기부활동의 장점으로 간편한 접근성, 낮은 기부 장벽, '좋아요·공유·댓글’ 등과 같은 간접기부 가능, 참여를 통한 상호작용을 꼽았다. 마지막으로, 기부를 하기 위한 고려사항으로는 진정성과 관심도와 같은 내적요인과 기부단체에 대한 투명성과 신뢰성과 같은 외적요인들이 존재한다는 것이 밝혀졌다. This study investigated the motives and reasons for university students' donations, as well as the advantages of social media (SNS) donations and considerations when engaging in SNS donations through in-depth interviews. The results of the study revealed that donation motives were divided into intrinsic and extrinsic motives. Intrinsic motives included altruism, empathy, and a sense of social responsibility, reflecting internal values and motivations. Extrinsic motives encompassed influences such as recommendations from acquaintances, advertisements, family encouragement, and celebrities' donation activities. The reasons for university students' donations coexisted between pure altruistic motives, based on the belief that their contributions would contribute to the development of a mature society, and altruistic reasons derived from the pride of making donations that could benefit society. The advantages of SNS donation activities highlighted by university students included easy accessibility, low donation barriers, the possibility of indirect donations through actions like likes, shares, and comments, as well as interaction through participation. Finally, the considerations for making donations included intrinsic factors such as sincerity and interest, as well as extrinsic factors such as transparency and trustworthiness of the donation organization. The study emphasized the importance of genuine intentions and interest from donors, along with the transparency and trustworthiness of the organizations involved, as crucial factors in the decision-making process for donations. KCI Citation Count: 0